Analysis of repeated lesions after diabetic forefoot amputation. (August 2022) - Choi, Youngrak; Lee, Ho Seong; Kim, Ji Wan; Lee, Bum-Sik; Lee, Woo Je; Jung, Hong-Geun
Abstract: Aim: This study was performed to analyze the clinical characteristics, related factors, and prognosis of repeated lesions after diabetic forefoot amputation. Methods: The medical records of 998 patients who underwent forefoot amputation because of their diabetic feet from March 2002 to February 2021 were retrospectively analyzed. Of the 508 selected patients with a follow-up period of at least 6 months, 288 had repeated lesions in the forefoot, and 220 did not have repeated lesions. The related factors of repeated lesions were compared and analyzed. Of the patients with repeated lesions, 142 and 104 on the ipsilateral and contralateral sides, respectively were also compared and examined. Results: Repeated lesions were statistically significant in diabetic polyneuropathy, vascular calcification, and dialysis. However, the anatomical positions of diabetic foot lesions, causes of lesions, anatomical amputation levels, number of surgeries, and management duration had no significant differences. Contralateral lesions occurred 8 months later than ipsilateral lesions, but reamputation above the Lisfranc joint was more frequent and prognosis was poorer. Conclusions: Repeated lesions were affected by general conditions, and the contralateral side must be carefully examined after diabetic forefoot amputation.